PELATIHAN PENERAPAN SISTEM E-ARSIP SURAT UNTUK MENINGKATKAN EFISIENSI PENGELOLAAN SURAT DI DPMPTSP KUDUS - Firmansyah, Heru Noviyanto; Muzid, Syafiul (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The manual letter management in DPMPTSP Kudus makes the administrative process time-consuming, prone to errors, and archiving is not easy to search. There needs to be an improvement to increase efficiency in correspondence management. One of the solutions that can be applied is an e-archiving system that is able to reduce the use of paper, offer convenience in searching data, and speed up the archiving process. The method used in this service is training in the use of the e-archive system to DPMPTSP Kudus staff, including the use of the digital archiving system and procedures. The results of the service show that the utilization of this system can make the management of archives more efficient, reduce errors in archiving, and make mail data more retrievable. The utilization of the e-archive system is expected to be a gateway to digital transformation in government institutions.